Healthcare professionals' perceptions of the value and impact of the arts in healthcare settings: A critical review of the literature. (April 2016) - Wilson, Ceri; Bungay, Hilary; Munn-Giddings, Carol; Boyce, Melanie
Abstract: Background: Internationally there is growing interest in the use of the arts in the healthcare context evidenced by the number of research studies reported in the nursing and medical literature. Establishing successful projects in healthcare environments will to some extent be reliant on the cooperation of staff working in these settings: healthcare professionals and their cultural values will be the lynchpin in the relationship between the artists organising the activities and the patients. This review appraises healthcare professionals' perceptions of the value of the arts in healthcare settings, and the impact of the arts on healthcare professionals. Methods: A critical review of the literature between 2004 and 2014 was undertaken. The following databases were searched: MedLine, CINAHL, AMED, Web of Science and ASSIA. Searches included words from three categories: arts activities; healthcare settings, and healthcare providers. Studies were included if they were written in English, explored the attitudes of healthcare professionals on the use of the arts in healthcare settings or the impact of arts activities on healthcare staff. Studies conducted in community venues and/or reporting on arts therapies (art, drama or music) were excluded. An initial 52 studies were identified and following screening for relevance and quality 27 articles were reviewed. Arts interventions were diverse and included music listening, visual arts, reading and creative writing, and dance. Results: Despite some methodological limitations of the reviewed studies it was found that the majority of staff believed that engaging in arts interventions has a positive impact on patients' health and well-being. The findings suggest that arts interventions are perceived to have an impact on patients' stress, mood, pain levels, and sleep. Furthermore, staff believed that the arts can enhance communication between staff and patients, helping to build rapport and strengthen interactions. The majority of reported staff outcomes were positive, with arts activities in healthcare settings found to: decrease stress, improve mood, improve job performance, reduce burnout, improve patient/staff relationships, improve the working environment and improve well-being. Conclusions: This review fills a gap in the literature, providing the first review of healthcare professional's views of the arts in healthcare settings and the impact of arts activities on healthcare staff. The largely positive perceptions of staff will aid in the implementation of arts activities in healthcare settings, which will enhance care and benefit both patients and healthcare staff.